Risk factors for intraventricular hemorrhage in very low birth weight infants: a systematic review and meta-analysis - Bao, Liming; Huang, Jinyan (Frontiers in Pediatrics, 2026)
BackgroundIntraventricular Hemorrhage (IVH) is one of the common and serious complications of Very Low Birth Weight Infant (VLBW) that may lead to long-term neurodevelopmental deficits. Although several studies have been conducted to explore its risk factors, the results have been inconsistent. The aim of this study was to identify the major risk factors for intraventricular Hemorrhage in VLBW by systematic evaluation and Meta-analysis of the available evidence.MethodsPubMed, Web of Science, Embase, Cochrane Library were systematically searched, and observational studies (case-control and cohort studies) were included from the time of library construction to 20 January 2025, and the literature that met the criteria were screened and relevant data were extracted. Meta-analysis was performed using Stata 15.0 software to assess the combined odds ratio (OR) and 95% confidence interval (CI) for each risk factor.ResultsA total of 21 studies included 6 case-control studies, 15 cohort studies, involving a total of 13,800 patients, The results of the meta-analysis showed that hypotension [OR = 3.64, 95%CI (1.87, 7.08)], patent ductus arteriosus (PDA) [OR = 1.86, 95%CI (1.46, 2.36)], vaginal delivery [OR = .10, 95%CI (1.61, 2.72)], neonatal thrombocytopenia[OR = 2.43, 95%CI (1.79, 3.30)], pulmonary hemorrhage [OR = 2.45, 95%CI (1.43, 4.20)], mechanical [OR = 2.09, 95%CI (1.40, 3.10)], sepsis[OR = 2.28, 95%CI (1.77, 2.95)] were a risk factor for the development of IVH in VLBW. While antenatal corticosteroids [OR = 0.68, 95%CI (0.55, 0.84)] was a protective factor for the development of IVH in VLBW.ConclusionThis study indicates that hypotension, patent ductus arteriosus (PDA), antenatal corticosteroid use, vaginal delivery, neonatal thrombocytopenia, pulmonary hemorrhage, mechanical ventilation, and sepsis constitute the primary risk factors for IVH in VLBW infants. Although these factors exhibit strong clinical associations, current understanding of IVH pathogenesis remains largely dependent on preclinical studies. Integrating clinical and preclinical evidence facilitates a more comprehensive understanding of IVH etiology and informs early intervention strategies.Systematic Review Registrationidentifier CRD42025633474.